Analisa Peluang dan Ancaman Perdagangan Bebas Produk Pertanian Sektor Kelapa Sawit (Studi Kasus Perdagangan Indonesia dengan Malaysia) - Santosa, Nugraha Budi; Purnamasari, Pupung; Doni , Doni; Nur Iklima , Faradila (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Free trade has become a major focus in the international economy, with significant impacts on the agricultural sector, including palm oil. This analysis aims to evaluate the opportunities and threats faced by the palm oil sector in the context of free trade. In this analysis, opportunities such as wider market access and increased global demand for palm oil are taken into account. However, those opportunities can also be balanced with threats such as increased competition from other producers, changes in environmental regulations, and pressure from sustainability- related advocacy groups. Indonesia and Malaysia cooperate in the palm oil commodity sector. In this study the author uses demand theory, bilateral economic cooperation, and interdependence to analyze the study in it, and in this type of research writing uses descriptive- quantitative to process existing data. One of the solid export performance of the agricultural sector is dominated by palm oil commodities as the top of exports. Through a comprehensive approach to these opportunities and threats, stakeholders in the palm oil sector can take strategic steps to strengthen their position in the global market, while also paying attention to its impact on environmental and social sustainability.